On training and performance : traces of an Odin teatret actress - Carreri, Roberta, 1953- (Routledge, 2014)
Interwoven with photographic documentation and a wealth of biographical information, this handbook reveals the professional secrets of an Odin Teatret actor as well as the story of a life of work, research, and passion.